Avaliação de danos em edificações públicas do município de Pau dos Ferros/RN através de inspeções visuais e aplicação da metodologia GDE/UNB - Barra, Bárbara Beatriz Melo (Universidade Federal Rural do Semi-Árido, 2017)
Several public buildings have great relevance within a historical context of a given city, which are constructed with techniques, often different from those commonly used today. In view of this, during its uses over time; There has been the appearance of pathological manifestations, especially in reinforced concrete structures, which significantly affect durability, in this sense research on the degree of deterioration, as well as maintenance and repair services are essential. Thus, due to the presence of pathological manifestations in public buildings in the city of Pau dos Ferros / RN, a study was made of the state of conservation of some buildings in relation to their functionality, aesthetics and durability. For this, in this research, were chosen buildings that are of great contribution to the municipality. With this, were chosen three buildings: State School September 4, Municipal Butchery of Pau dos Ferros/RN, And the Kiosks of Matriz Square, being public buildings of great use, that supports a great number of people. For this study, on-site inspections were carried out and applied to the GDE / UnB Methodology of Fonseca (2007), to quantify the degree of deterioration of the structures. Due to the methodology studied, it was possible to verify the high level of deterioration of the structures, with the most deteriorated Pau dos Ferros / RN, reaching the critical level of deterioration, leading to a short term intervention for the solution of the present pathological manifestations . Faced with the damages observed in the buildings studied, it was verified that the main manifestations present in the buildings were: fissures, efflorescences and humidity spots.
Keywords: Manifestações Patológicas; Pathological Manifestations; Durabilidade; Durability; Deterioração; Deterioration; Estruturas de Concreto Armado; Reinforced Concrete Structures; Estado de Conservação; State of Conservation; ENGENHARIAS::ENGENHARIA CIVIL